2016
DOI: 10.1089/dia.2015.0432
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Infusion Set Survival in Lipohypertrophy Versus Nonlipohypertrophied Tissue in Patients with Type 1 Diabetes

Abstract: Background: Improved insulin infusion set survival and faster insulin action are important issues for pump users and for the development of an artificial pancreas. The current recommendation is to change infusion sets every 3 days. Our objectives were to determine the effect of lipohypertrophy (LH) on infusion set survival and continuous glucose monitoring glucose levels. Research Design and Methods: In this multicenter crossover trial, we recruited 20 subjects (age 28.1 -9.0 years) with type 1 diabetes (durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 24 publications
2
33
1
Order By: Relevance
“…Several previous studies investigating the impact of prolonged IIS wear have shown that whereas the risk of IIS failure rises with the length of time a unit is worn, the mean glucose and TDD do not change between day 1 and day 7 of IIS wear (33,34). Similar results were seen in this study whereby the day of the study did not appear to impact the mean glucose or the percent time in hypoglycemia (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Several previous studies investigating the impact of prolonged IIS wear have shown that whereas the risk of IIS failure rises with the length of time a unit is worn, the mean glucose and TDD do not change between day 1 and day 7 of IIS wear (33,34). Similar results were seen in this study whereby the day of the study did not appear to impact the mean glucose or the percent time in hypoglycemia (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Studies have shown that some patients indeed successfully wear CSII catheters up to 7 days. 19 , 24 In contrast, the ICs produced the highest AUC, AUC60, and C max on day 1, the fastest t max on day 3, and the lowest AUC, AUC60, and C max on day 5. Figures 1 and 2 illustrate the importance of reviewing the individual PK curves from each experiment to acknowledge the large dose-to-dose and day-to-day variability.…”
Section: Discussionmentioning
confidence: 88%
“…The primary mitigation of these faults is the widely accepted recommendation that insulin infusion sets are changed every three days. Since there is significant variability in the lifespan of these sets [34] many infusion sets are replaced before they need to be, driving up costs and increasing patient burden. Modern infusion pumps can monitor the back-pressure on an infusion catheter, but many LISA faults do not trigger these alarms.…”
Section: Control Algorithmsmentioning
confidence: 99%